Single-cell sequencing deciphers a convergent evolution of copy number alterations from primary to circulating tumor cells - Gao, Yan; Ni, Xiaohui; Guo, Hua; Su, Zhe; Ba, Yi; Tong, Zhongsheng; Guo, Zhi; Yao, Xin; Chen, Xixi; Yin, Jian; Yan, Zhao; Guo, Lin; et al. (Genome Research, 2017)
Copy number alteration (CNA) is a major contributor to genome instability, a hallmark of cancer. Here, we studied genomic alterations in single primary tumor cells and circulating tumor cells (CTCs) from the same patient. Single-nucleotide variants (SNVs) in single cells from both samples occurred sporadically, whereas CNAs among primary tumor cells emerged accumulatively rather than abruptly, converging toward the CNA in CTCs. Focal CNAs affecting the MYC gene and the PTEN gene were observed only in a minor portion of primary tumor cells but were present in all CTCs, suggesting a strong selection toward metastasis. Single-cell structural variant (SV) analyses revealed a two-step mechanism, a complex rearrangement followed by gene amplification, for the simultaneous formation of anomalous CNAs in multiple chromosome regions. Integrative CNA analyses of 97 CTCs from 23 patients confirmed the convergence of CNAs and revealed single, concurrent, and mutually exclusive CNAs that could be the driving events in cancer metastasis.